Winning or losing in investor‐to‐state dispute resolution: The role of arbitrator bias and experience. Issue 4 (8th March 2018) - Donaubauer, Julian; Neumayer, Eric; Nunnenkamp, Peter
Abstract: When an investor sues a state for alleged breaches of its obligations under an investment treaty or a trade agreement with investment provisions, all that should matter for who wins the case are the merits of the claim itself. Alas, investor‐to‐state dispute settlement (ISDS) does not take place in a vacuum. Such cases are decided by a tribunal typically consisting of three arbitrators, one each nominated by the two parties while the president is mutually agreed upon. We demonstrate that the kind of involvement of these arbitrators in previous ISDS cases matters for the case under dispute. Specifically, we show that what we label the presidents' pro‐investor appointment bias—the number of times they have previously been nominated by an investor minus the number of times they have represented respondent states—raises the likelihood that an investor wins an ISDS case. The same holds for the pro‐investor appointment bias of state‐appointed arbitrators. Given the president's crucial role, the main implication of our findings is that presidents should be drawn from among those who have not systematically represented more one side than the other in previous cases.